Workplace sexual harassment, individual factors - Malvin Tan Ping Chieng; Sharon Kwan Sam Mee (Fakulti Psikologi dan Pendidikan, 2021)
Workplace sexual harassment in Malaysian organizations has been under the spotlight since its exposure by local media recently. Previous research studies suggested that workplace sexual harassment has evolved with the conduct aiming to condescend victims. The focus of this current research study was to explore the individual factors that caused sexual harassment in Malaysia organizations. Interview data from 20 participants who were recruited using purposive random sampling from 20 various Malaysian organizations has been analyzed using Grounded Theory Methodology (Glaser and Strauss, 1976). The study explored two major individual factors that contributed to sexual harassment at work. There are perception and attitude of both victims and perpetrators. We found the differences between the perpetrator’s perception and the victim’s perception towards sexual harassment. Apart of physical harassment, victims considered subjective jokes (verbal), showing obscene hand gesture (non-verbal), and showing inappropriate pictures or messages (multimedia) behaviours are sexual harassment. However, the victims considered verbal, non-verbal, and multimedia harassment are less offensive and acceptable. The perpetrators also perceived these harassment behaviors are less harmful and are acceptable by the victims. Most of the victims tended to ignore and keep silent when these sexual behaviors happened, aimed to avoid any further troubles at the workplace. Eventually, it was too late for the victims to take action when it prolonged. The attitude of ignoring and keeping silent did not stop the perpetrators, in contrast, it encouraged the perpetrators to keep harassing and lead to more severe harassment such as physical and desire for intimacy sexual harassment. The victims only tended to voice or report to the organizations when they encountered physical harassment. The victims need to report and voice to the organization if there is any sexual harassment occurs at the workplace. Both the employees and organizations should actively work together to ensure a better working environment for the employees by providing support and cultivating an organizational climate that is hostile towards workplace sexual harassment.